Research software system for electronic health records deployed in hospitals - Đỗ, Thị Tú Uyên ([s.l], 2020)
The research focuses on promoting and applying IT in hospitals under Ministry of Health in prescribing electronic medicines, electronic patient records, and hospital management, establishing a support system for diagnosis. To reduce the burden on patients, to reduce the overload of hospitals at the central level. The report was developed for the treatment of eczema as a legal document on medical activity in patients. Electronic medical records support research: clinical, health care, drug effects. . .